Beyond Reconciliation: A Mubādalah-Based Victim-Centred Legitimacy Test for Islāḥ and Restorative Justice in Indonesian Domestic Violence Cases - Radin Ahmad Taufik Salikin Izaddin; Vivi Purnamawati (Journal of Islamic Mubadalah, 2026)
Domestic violence (DV) is frequently resolved through reconciliation, either within the framework of restorative justice or through the concept of iṣlāḥ, owing to its occurrence within ongoing personal and familial relationships. However, reconciliation is not always a neutral mechanism; it may function as an instrument of coercion against victims when conducted under conditions of economic dependency, psychological trauma, social stigma, and unequal power relations. This study examines the normative boundaries of integrating iṣlāḥ, restorative justice, and mubādalah theory in the resolution of domestic violence cases by positioning victim protection as the primary parameter of legitimacy. The research employs a normative legal method using conceptual and statutory approaches, analyzing Law No. 23 of 2004 on the Elimination of Domestic Violence, restorative justice regulations, judicial decisions, and Islamic legal literature concerning iṣlāḥ, maṣlaḥah, maqāṣid al-sharī‘ah, and mubādalah. The findings demonstrate that iṣlāḥ should not be construed as a moral obligation to preserve the family unit at all costs; rather, it constitutes a conditional mechanism that must be aligned with the principles of reciprocity, relational justice, victim safety, autonomy, and voluntariness. This article proposes a victim-centred mubādalah-based legitimacy test comprising risk assessment, independent assistance, informed written consent, offender accountability, and institutional oversight to prevent revictimization. This framework may serve as a practical guideline for judges, mediators, law enforcement officials, and victim-support institutions involved in domestic violence cases.